Penerapan Evidence Based Practice Terapi Infrared Terhadap Penurunan Nyeri Pada Lansia Dengan Osteoarthritis - Aulia Gawara; Kina Hutajulu; Agrina Agrina (JUKEJ : Jurnal Kesehatan Jompa, 2023)
Introduction An elderly person will experience many obstacles in his life when he enters an increasingly old age. These constraints can affect the health of the elderly both physically and mentally. Disrupted health can trigger a decrease in the quality of life of the elderly. Health problems that are experienced by many elderly people in lower-middle-income countries are musculoskeletal pain. The purpose of implementing evidence-based practice is to apply evidence-based applications in nursing practice by providing infrared therapy to the elderly with osteoarthritis. This method of applying evidence based practice was carried out in the people of Kemang Village, Pelalawan Regency who experienced pain in the extremities of the body and had been diagnosed with osteoarthritis in previous treatment. Analysis on evidence based practice uses PICO (Patient/Problem, Intervention, Compare and Outcome) analysis. In this evidence-based practice, the intervention that will be carried out is by giving infrared therapy rays 3 times a week for 3 weeks with a duration of 10 minutes to the elderly who experience joint pain in the knee. Conclusion: The application of evidence based practice with infrared therapy in the elderly with osteoarthritis is very effective and useful in reducing pain scores so that EBP can be used as a follow-up intervention for health workers in reducing knee pain in the elderly with osteoarthritis.